Digitalization of BUMDes Management as a Performance Driver towards Digital Villages - Darma Sanputra, Adrian Hartanto; Miftakh, Eliza Silviana; Kusna, Silfi Hidayatul; Agustin, Wanda Tri (International Journal of Public Devotion, 2024)
The development of digital technology, particularly websites, as promotional and communication media is currently widely utilized by several Village-Owned Enterprises (BUMDes). However, many BUMDes still lack a website presence, including those in Sumberpucung Sub-district. This study aims to assist villages in Sumberpucung Sub-district in maximizing their economic potential and increasing village revenue through product branding strategies, enabling these villages to evolve into more independent and competitive digital villages. The methodology employed includes observation, Focus Group Discussions (FGD), socialization, technical guidance and training, and handover. Participants in this activity were 8 BUMDes within Sumberpucung Sub-district. The initiative successfully increased awareness and understanding among village officials regarding the importance of product branding and digitalization in supporting village economic potential. The collaboration established between village governments and the Sumberpucung Sub-district Head also strengthened sustainable village economic management. This community service project possesses originality in combining product branding strategies with digitalization through the implementation of website-based BUMDes applications, which had not been comprehensively undertaken in the villages of Sumberpucung Sub-district previously. The added value lies in the collaborative approach involving sub-district and village governments, thus creating an ecosystem that supports digital transformation at the village level.